Atrial Oversensing by an LV Lead during Typical Flutter: The Interest of Electronic Repositioning. Issue 2 (28th April 2011) - DUPARC, ALEXANDRE; MONDOLY, PIERRE; DETIS, NICOLAS; CHILON, TALIA; ROLIN, ANNE; MAURY, PHILIPPE; DELAY, MARC
<x xml:space="preserve">Abstract</x> Occurrence of supraventricular tachycardia is a common cause of clinical impairment for patients implanted with CRT devices. We report the case of atrial activity oversensing by the left ventricular (LV) lead during typical flutter, which led to LV pacing inhibition. Temporary reprogramming of the LV detection from standard bipolar to extended bipolar and cavotricuspid isthmus ablation solved this problem. (PACE 2013; 36:e53–e55)